The Effects on Online Learning on EFL students' English Oral Comprehension Case of Third Year English Students at Mohamed-Cherif Messaadia - Bouaargoub Chaima (My University, 2022)
Abstract: This study intends to demonstrate how oral Comprehension is taught in this pandemic, what tool may be used online to replace face-to-face oral teaching, and what impact this kind of teaching has on student speaking performance. Furthermore, this research demonstrates which teaching method is more helpful in developing students' communicative competence, self-confidence, and ability to apply their newly gained knowledge. To achieve this goal, the researcher used two basic methods: a questionnaire and observation, to conduct a survey of third-year English-language license students. According to the findings of these two studies, teachers should ask for recorded oral presentations as a tool for teaching and assessing oral expression online. Eventually, face-to-face teaching cannot be substituted by another distant method, but the two forms can work together to promote proper EFL teaching and learning.